Laboratory Hydraulic Fracturing of Large-Scale Granite Characterized by Acoustic Emission Under Different Confining Conditions - Wang, Huang; Wang, Guiling; Chen, Yuedu; Liu, Lu; Zhao, Zhihong; Gan, Haonan (Frontiers in Earth Science, 2022)
Hydraulic fracturing (HF) technology is crucial to form connected fracture network within the low-permeability geothermal reservoir. However, the HF process and failure mechanism in this process are only partly understood. A series of true triaxial hydraulic fracturing tests on large-scale natural granite samples were conducted under different confining conditions, combining with acoustic emission monitoring to evaluate the initiation and propagation of hydraulic fractures. Results show that a main hydro-fracture was formed in three samples during the first fracturing process. Many AE events occurred during the first pump period. The proportion of tensile fractures during the hydraulic fracturing accounted for more than 85% of all fractures. The test results could provide a new understanding of the effect of HF under different stress conditions. And implied that field engineering should pay attention to the initial HF, which may determine the main fracture framework of the field at the first pump procedure.